Sosialisasi Pengenalan Media Pembelajaran Kahoot untuk Anak Sekolah Minggu di Gereja HKBP Resort Dame - Simanjuntak, Ruth Mayasari; Putri, Nuryosianna; Simanullang, Dinda S.; Simanjuntak, Meissy Adelina (Pakis Journal Institute, 2026)
This community service activity aims to introduce and implement Kahoot as a digital learning media to improve the learning interest of Sunday School children at HKBP Resort Dame Church. The background of this activity is the lack of variation in teaching methods, which tends to be monotonous and less engaging for children. The method used includes socialization, training, and direct practice of using Kahoot in the learning process. The results show that the use of Kahoot significantly increases students’ enthusiasm, participation, and motivation. Children become more active and interested because the learning process is packaged in an interactive and fun way. In addition, teachers gain new insights into the use of digital learning media. Thus, Kahoot can be an effective alternative learning media to support interactive and innovative teaching.